Effects of relationship with socialization agents and acceptance of multiculturalism on prosocial behavior of multicultural youth in South Korea - CHOI, Goun (KDI School, 2016)
Korea, which has been historically an ethnically homogenous country, is encountering demographical change due to the influx of foreign population and international marriage. Multicultural family and youth are one of the vulnerable ethnic minorities in Korea in terms of access to social services and the economy. Korea needs to accept multicultural families as new citizens and redefine national identity and social cohesion for inclusive social development. Prosocial behavior can be an indicator to measure whether multicultural population understands and practices social norms, feels belongingness and responsibility, and would contribute as a member of society. In this regard, this research questions what would trigger prosocial behavior of multicultural youth and run multiple regression with variables of prosocial behavior, socialization agents such as parents, peer-group, and school, and acceptance of multiculturalism in school and residential area using interaction effects. The results of analyses are that positive relationship with socialization agents is related to elicit prosocial behavior of general Korean youth but not multicultural youth. Receptive social climate, however, leads to prosocial behavior of multicultural youth, which implies the significance of creating an open society to multiculturalism for adaptation of multicultural youth
Thesis(Master) --KDI School:Master of Development Policy,2016